Students’ assessment and class management: A critical Approach - Balla, Ervin (European Journal of Sustainable Development, 2014)
We know that the teaching method is effective only if it reaches the targets of the program. Teaching the students in each level should be tested. The assessment and the testing of the students are important parts of teaching and learning process. The students learn very well in classes is constant and is part of student’s expectations. The assessment can be done in various ways, through testing at the end of the term, or can be done continuously. However testing and assessment should be taken really seriously if we want to achieve high results in our work as English teachers. Also the class management plays an important part in the process of teaching-leaning and it is closely connected to the assessment and testing of the students. Key words: assessment, class management, teaching, learning. testing